Redefining School Libraries for the Digital Age: Developing Comprehensive Digital Collection Strategies - Hasibuan, Putri Aisyah; Fadhli, Rahmat; Igiriza, Miftahunnisa' (Jurnal Manajemen Pendidikan : Jurnal Ilmiah Administrasi, Manajemen dan Kepemimpinan Pendidikan, 2023)
This study aims to analyze the strategy for developing digital collections in school libraries. The method used is qualitative research with data collection techniques including observation, interviews, and documentation. The research was conducted at the Widura Library of Vocational High School 3 Yogyakarta. The study involved three informants, consisting of the head librarian and school library staff. The results show that the school library already has a digital collection as part of its development. The process of developing digital collections in school libraries includes analyzing user needs, mapping digital collection sources, and evaluating development. The development of digital collections is still limited to obtaining electronic school book collections from the Ministry of Education. Some strategies that can be implemented by school libraries include collaborating with other libraries and downloading digital collections that are available for free from digital collection providers.